2008
DOI: 10.1111/j.1349-7006.2007.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein–Barr virus antibody levels with precancerous gastric lesions in a high‐risk cohort

Abstract: We evaluated associations between Epstein-Barr virus (EBV) antibody levels and precancerous gastric lesions (chronic atrophic gastritis, intestinal metaplasia, and dysplasia) in 183 subjects from Linqu, China. Immunoglobulin G antibody titers to EBV nuclear antigen (EBNA) and viral capsid antigen (VCA) were determined by two-fold serial dilution using immunofluorescence assays. Histological progression and regression were assessed by gastroscopic examination at the time of phlebotomy and at follow up 2 years l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Interestingly, Tang et al 54 found that compared to uninfected tumours, EBV-positive gastric cancer had significant upregulation of key cellular factors in pathways related to NFKB signalling and immune response. Although seropositivity against EBV infection is nearly ubiquitous in humans, elevated titres against VCA and EBV nuclear antigen (EBNA) have been shown to precede development of preneoplastic55 and neoplastic gastric lesions,56 57 and have been associated with longer gastric cancer survival, particularly for cancers localised to the gastric cardia 58…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tang et al 54 found that compared to uninfected tumours, EBV-positive gastric cancer had significant upregulation of key cellular factors in pathways related to NFKB signalling and immune response. Although seropositivity against EBV infection is nearly ubiquitous in humans, elevated titres against VCA and EBV nuclear antigen (EBNA) have been shown to precede development of preneoplastic55 and neoplastic gastric lesions,56 57 and have been associated with longer gastric cancer survival, particularly for cancers localised to the gastric cardia 58…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Epstein–Barr virus (EBV) has been found in ∼9% of non-cardia gastric cancer cases worldwide 24. The mechanism by which EBV may contribute to gastric carcinogenesis is uncertain, but several lines of evidence support its aetiological role: (1) monoclonality of viral episomes in the tumour25; (2) distinct clinical features of EBV-carrying gastric carcinomas as compared with EBV-negative tumours26; (3) characteristic molecular markers, including specific chromosomal aberrations, a transcription pattern resembling but not identical to nasopharyngeal carcinomas, and expression of the EBV BARF1 gene27; and (4) EBV reactivation preceding clinical presentation of gastric precancerous or cancerous lesions, as indicated by elevated antibodies to viral capsid and nuclear antigens 28 29. EBV-positive tumours are preferentially located in the corpus and other non-antral portions of the stomach,24 30 which may have particular relevance for the shifting subsite distribution we detected.…”
Section: Discussionmentioning
confidence: 99%
“…EBV VCA titers ≥320 are considered elevated and are correlated with reactivation in immunosuppressed individuals (Horwitz et al, 1985; Jenson, 2011). Other investigators, using EBV VCA titers ≥640 as a cutoff, found an increased risk of disease progression (Schetter et al, 2008). Therefore, the EBV and CMV data was further analyzed by using both cutoffs (i.e., ≥320 and ≥640).…”
Section: Resultsmentioning
confidence: 99%